Rational design and characterization of lattice structures made from circular-arc curved bars. (January 2021) - Fu, Yutong; Liu, Wei
Highlights: A lattice structure made from circular-arc curved bars is designed. Theoretical models of the stiffness of lattice elements are established. Lattice structures exhibit nonlinear and tunable properties. Abstract: In this paper, a lattice structure whose mechanical properties can be systematically designed is presented using tailored sub-unit structures made from curved bars. First, the stiffness of circular-arc curved bars is theoretically studied, and the effects of geometric parameters of the curved bars on the mechanical properties are analyzed. Second, sub-unit structures are designed based on the fractal geometry, and periodic structures for lattice structures assembled from different sub-unit structures are precisely fabricated using 3D printing techniques. Third, mechanical properties of structures are mechanically measured and numerically simulated simultaneously, which present anisotropy of stiffness depending on the loading direction. These results show that the controllable stiffness of lattice structures along different directions can be designed by changing structure geometry and degrees of fractal. This study proposes a new method for the design of lattice structures and potential in versatile industrial and biomedical applications.